Pengetahuan, Uang Saku dan Peranan Media terhadap Kejadian Kekurangan Energi Kronis (KEK) - Siti Isnaeni; Ari Yuniastuti; Oktia Woro Kasmini Handayani (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the factors of knowledge, pocket money, and the role of the media on the occurrence of KEK. This research method is an observational analytic study using a cross-sectional design (cross-sectional). The result of the analysis is that knowledge affects KEK with a T count of 4.134 and a significance value of 0.000. The role of the media does not affect the incidence of KEK, with a calculated T value of 0.166 and a significance of 0.868. In conclusion, pocket money affects KEK with a T count of 2.431 and a significance value of 0.016. With good knowledge and supported by students' financial conditions, students can determine a good diet and make their upper arm circumference exceed 23.5. Keywords: KEK, Knowledge, Role of Media, Pocket Money